2020
DOI: 10.1038/s41598-020-75618-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100B protein as a marker of severity in Covid-19 patients

Abstract: SARS-CoV-2 infection shows a wide-ranging clinical severity, requiring prognostic markers. We focused on S100B, a calcium-binding protein present in biological fluids, being a reliable biomarker in disorders having inflammatory processes as common basis and RAGE as main receptor. Since Covid-19 is characterized by a potent inflammatory response also involving RAGE, we tested if S100B serum levels were related to disease severity. Serum samples (n = 74) were collected from hospitalized SARS-CoV-2 positive patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 36 publications
7
66
2
1
Order By: Relevance
“…Another study found that 63% of patients had high ferritin levels [12] . Another study reported that the S100B protein could be used as a biomarker in severe COVID-19 patients and correlated with ferritin [10] . In this study, a significant increase was observed in ferritin levels in PCR-positive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that 63% of patients had high ferritin levels [12] . Another study reported that the S100B protein could be used as a biomarker in severe COVID-19 patients and correlated with ferritin [10] . In this study, a significant increase was observed in ferritin levels in PCR-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study has reported that neutralizing antibodies play a crucial role in identifying COVID-19 infection [9] . Another study claimed that serum S100B protein could be a crucial marker in the diagnosis of severe COVID-19 [10] . However, Zeng et al reported that serum interleukin (IL)-2 receptor, IL-6, IL-8, IL-10, tumor necrosis factor-alpha (TNF-α), ferritin, procalcitonin lactate dehydrogenase, and high-sensitive C-reactive protein (hsCRP) were higher in critically ill patients than moderate and severe patients [11] .…”
Section: Introductionmentioning
confidence: 99%
“… 41 Third, serum S100B levels were associated with increased disease severity and COVID-19 score in affected patients. 42 Fourth, in extracellular vesicles, significantly higher levels of S100A12 were observed in patients with severe versus moderate COVID-19. 43 Fifth, higher levels of S100A8/A9 and a distinct DAMP RAGE ligand, HMGB1, were found to associate with higher risk of intensive care unit admission and death in patients with COVID-19.…”
Section: Rage—from Its Discovery In the Endothelium And Onwardsmentioning
confidence: 83%
“…Furthermore, astrocytes regulate the permeability of BBB through influencing expression of tight junctions in endothelial cells layer (Kriauciunaite et al, 2020 ). Serum levels of the astrocytic calcium binding protein S100b, associated with an increased BBB permeability, significantly correlate with COVID-19 disease severity, inflammation markers (ferritin, C-Reactive Protein, procalcitonin), and organ damage markers (alanine aminotransferase, creatinine) (Aceti et al, 2020 ). S100b is a calcium binding protein, strongly expressed in astrocytic endfeet lining the BBB; genetic deletion of S100b is associated with age-dependent increase in BBB leakage (Wu et al, 2016 ).…”
Section: Astrocytes and Microglia: The Gatekeepers And Defenders Of Tmentioning
confidence: 99%